Visceral analgesia with continuous infusion of maropitant in bitches undergoing ovarian salpingohysterectomy - Yoshioka, Patrícia Da Silva; Monteiro, Jordana Casemiro Pinto (Pubvet, 2023)
Maropitant is used in dogs and cats as an antiemetic, with its antagonistic action being on NK-1 receptors, and its closest ligand being the neuropeptide known as substance P, which plays a primary role in the transmission and maintenance of nociceptive information. Thus, inhibiting the release of this substance is considered a conduit to effective analgesia. The objective of this work was to evaluate the analgesic efficacy of maropitant in two bitches undergoing ovarian salpingohysterectomy
Keywords: dogs; infusion; maropitant; ovariosalpingohisterectomy